Use of naloxone by EMS for opioid-associated out-of-hospital cardiac arrest and associated patient-centered outcomes: A systematic review - Hania Siddiqui; Khadija Brouillette; Chris Walsh; Sheldon Cheskes; Ian R. Drennan; Charles D.G. Keown-Stoneman; Steve Lin; Rohit Mohindra (PLoS ONE, 2026)
Objective As opioid-related fatalities continue to climb, it is imperative to advance our understanding of the management of life-threatening opioid emergencies, including cardiac arrest. Emergency medical services (EMS) administered naloxone reverses critical respiratory depression within minutes; however, the role of naloxone in cases of opioid-associated cardiac arrest (OA-OHCA) is unknown. This systematic review sought to summarize patient outcomes following EMS-administered naloxone in OA-OHCA cases. Methods Following PRISMA guidelines, a systematic search was conducted in OVID Medline, Embase, and Cochrane from database inception to December 2024. Original, peer-reviewed studies examining patients with OA-OHCA who were given naloxone by EMS were included. Two independent reviewers screened titles/abstracts and full-texts in Covidence based on predetermined inclusion criteria. Relevant data points were extracted, and a risk of bias assessment was conducted for included studies. No meta-analysis was performed due to heterogeneity across the included studies. Results The literature search yielded 4814 articles, of which 8 studies met eligibility and were included. Seven of the included studies were retrospective cohort studies conducted in the United States. The eighth included study was a prospective cohort study conducted in Denmark. The total sample size for drug-related OHCA patients was 1294 (range 16–471) from all the included studies. Risk of bias was assessed to be low to moderate in seven studies and serious in one study. A minority of patients achieved return of spontaneous circulation (ROSC), with ROSC ranging from 4.3% to 50%. Survival to hospital admission ranged from 11.1% to 55%, while survival to hospital discharge ranged from 0% to 20.4%. Conclusions There are a limited number of studies assessing the use of naloxone in patients who present in opioid-associated out-of-hospital cardiac arrest (OA-OHCA). Further research is needed to evaluate the effectiveness of naloxone in this patient population.